Epicutaneous patch testing in drug hypersensitivity syndrome (DRESS) - Santiago, F (2010)
BACKGROUND: In some patterns of cutaneous adverse drug reactions, and depending on the culprit drug, patch testing has been helpful in confirming its cause. Its value in Drug Rash with Eosinophilia and Systemic Symptoms (DRESS) has not been established in a large cohort of patients. OBJECTIVE: The aim of the present study is to evaluate the safety and usefulness of patch testing in DRESS. PATIENTS/METHODS: Between January 1998 and December 2008, we studied 56 patients with DRESS induced by antiepileptic agents in 33 patients (59%), allopurinol in 19 (34%) and sulfasalazine, cotrimoxazole, tenoxicam, and amoxicillin in 1 patient each (7%). RESULTS: A positive patch test reaction was observed in 18 patients (32.1%), of which 17 were with antiepileptics and 1 with tenoxicam. In the antiepileptic group, carbamazepine alone was responsible for 13 of 17 positive reactions (76.5%). Patch tests with allopurinol and its metabolite were negative in all cases attributed to this drug. CONCLUSIONS: In this study, patch testing was a safe and useful method in confirming the culprit drug in DRESS induced by antiepileptic drugs, whereas it had no value in DRESS induced by allopurinol. The pathogenesis of DRESS is not yet entirely clarified, but positive patch tests suggest a drug-dependent delayed hypersensitivity mechanism.